Analisis Hukum terhadap Penetapan Kuasa Asuh Anak sebagai Akibat Perceraian (Analisa Hukum Pasal 156 Kompilasi Hukum Islam) - Maryanih Maryanih; Andi Akram; Syarif Fadillah (Fakultas Hukum, Universitas Islam As-Syafi'iyah, 2021)
Divorce has legal consequences, such the distribution of marital property, and child custody. In the Compilation of Islamic Law, child custody must be seen from the child condition, where in the provisions of Article 105, it is known that child custody must see whether the condition of mummayiz or not. For children who are not yet mummayiz, the custody of the child is given priority to the biological mother, but it is not uncommon where in divorce cases, the child is not yet mummayiz, the custody rights are delegated to his biological father, so the purpopse in this study, is intended to examine and analyzing the position of child custody due to legal divorce consequences according to the Compilation of Islamic Law and who has the right of child custody due to legal consequences of divorce. This study uses a normative research method, with the data used is secondary in the form of library data. The results of the study indicate that the position of parents in child custody due to the legal consequences of divorce according to the Compilation of Islamic Law, is based on Article 105 and Article 156 of the Compilation of Islamic Law, where the hadhanah of the child, the biological mother is preferred, but if there are certain conditions based on Article 156 of the Compilation Islamic law, where the hadhanah holder cannot guarantee the physical and spiritual safety of the child, of course the child's hadhanah can be transferred.